Research on the confinement mechanism and calculation method of axial load-bearing capacity of steel-reinforced concrete-filled square steel tubular columns - Cong Peng; Deprizon Syamsunur; Taha Mohammed Jassam; Zhiming Zhang (Discover Applied Sciences)
Abstract There are significant discrepancies between the experimental results and numerical analysis outcomes for steel-reinforced concrete-filled steel tubular (SRCFST) columns. This is primarily due to the lack of understanding of the confinement mechanisms of SRCFST and the corresponding models for confined concrete. Therefore, based on the confinement mechanisms of square steel tubes and steel reinforcements on concrete, this paper calculates the effective lateral confining stress to determine the strength enhancement factors for concrete in various confined regions. Drawing from the classical Mander model, the key parameters are modified to establish stress–strain models for concrete in different confined regions. By comparing and analyzing axial compression test data for steel tube-reinforced concrete short columns with different parameters, the study identifies the most suitable axial compression bearing capacity calculation formula for these columns. Additionally, the introduction of stress–strain models into finite element analysis, compared with experimental results, demonstrates that the proposed confinement mechanism and the established stress–strain model for steel-reinforced concrete are reasonable and effective. The theoretical calculation results for the ultimate bearing capacity based on this are well aligned with the simulation and experimental values.